SHAKESPEARE IN LITHUANIAN - Ema Vyroubalová; Gemma Navickiene (Mokslo Taikomieji Tyrimai Lietuvos Kolegijose)
Shakespeare’s plays and poetry have been translated into over one hundred languages and are performed, read, and taught throughout much of the world more often than those of any other playwright. The article aims to briefly survey the history of translating Shakespeare’s works into Lithuanian. Current developments in business, communication, and cultural production impact the scope and priorities of translations. Our archival research yielded limited information on Lithuanian translations of Shakespeare’s works and their quality. It raised more questions than provided answers. The findings show that the largest number of translations of Shakespeare’s works was made by Aleksys Churginas (published in 1946-1973). Four plays were translated by Antanas Danielius (published in 1983-1997). The two most recent translations by Saulius Repečka were published in 2016. No comprehensive studies of Lithuanian translations of Shakespeare’s plays or their publication/republication history currently exist. The translation of sonnets has been investigated in a doctoral thesis.